Nanoparticle-Mediated Drug Delivery for Treatment of Ischemic Heart Disease - Fan, Chengming; Joshi, Jyotsna; Li, Fan; Xu, Bing; Khan, Mahmood; Yang, Jinfu; Zhu, Wuqiang (Frontiers in Bioengineering and Biotechnology, 2020)
The regenerative capacity of an adult cardiac tissue is insufficient to repair the massive loss of heart tissue, particularly cardiomyocytes (CMs), following ischemia or other catastrophic myocardial injuries. The delivery methods of therapeutics agents, such as small molecules, growth factors, exosomes, cells and engineered tissues have significantly advanced in medical science. Furthermore, with the controlled release characteristics, nanoparticle (NP) systems carrying drugs are promising in enhancing cardioprotective potential of drugs in patients with cardiac ischemic events. NPs can provide sustained exposure precisely to the infarcted heart via direct intramyocardial injection or intravenous injection with active targets. In this review, we present the recent advances and challenges of different types of NPs loaded with agents for the repair of myocardial infarcted heart tissue.